2022
DOI: 10.1126/sciadv.abo1215
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of FAM134C by CK2 controls starvation-induced ER-phagy

Abstract: Selective degradation of the endoplasmic reticulum (ER) via autophagy (ER-phagy) is initiated by ER-phagy receptors, which facilitate the incorporation of ER fragments into autophagosomes. FAM134 reticulon family proteins (FAM134A, FAM134B, and FAM134C) are ER-phagy receptors with structural similarities and nonredundant functions. Whether they respond differentially to the stimulation of ER-phagy is unknown. Here, we describe an activation mechanism unique to FAM134C during starvation. In fed conditions, FAM1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Importantly, unlike FAM134B where BafA1 treatment considerably reduced the basal flux, the basal FAM134C-associated TOLLES:YPet index was not affected by autophagy block. This highlights the low FAM134C-degradation levels in basal conditions (i.e., low TOLLES-positive and YPet-negative puncta), consistent with previously reported studies [ 41 , 42 , 43 , 44 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Importantly, unlike FAM134B where BafA1 treatment considerably reduced the basal flux, the basal FAM134C-associated TOLLES:YPet index was not affected by autophagy block. This highlights the low FAM134C-degradation levels in basal conditions (i.e., low TOLLES-positive and YPet-negative puncta), consistent with previously reported studies [ 41 , 42 , 43 , 44 ].…”
Section: Resultssupporting
confidence: 92%
“…They cooperate with quality-control pathways such as ER-associated protein degradation (ERAD) or UPR [ 35 , 40 ], and these SRAI-based reporters could be used to explore these stimuli. In this study, we used different ER-phagy receptors to analyze ER-phagy receptor flux and we observed that they all responded to nutrient starvation as previously reported [ 24 , 31 , 36 , 41 , 42 , 43 , 44 ]. Furthermore, we also observed some differences between the receptors such as the low basal degradation levels of the ER-phagy receptor FAM134C in comparison to FAM134B as previously reported [ 43 ].…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…FAM134B binds to ATG8 through its AIM domain to recruit the IM and promote ER-phagy ( Figure 3 b). The FAM134 reticulon family proteins (FAM134A/B/C) have a similar structure and function, and all act as receptors [ 116 ]. However, there are some differences.…”
Section: Membrane Curvature In Selective Autophagymentioning
confidence: 99%